The role of T cells in the pathogenesis and prevention of the inflammatory and neurodegenerative changes associated with Alzheimer's disease - McQuillan, Keith (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2009)
Alzheimer’s disease (AD) is a neurodegenerative disease, which is characterised by deposition of amyloid-beta (Aβ)-containing plaques and also by neuroinflammatory changes, typified by an increase in proinflammatory cytokine expression in the brain. Activated microglia are considered to be the major source of proinflammatory cytokines in AD, and recent studies have highlighted the importance of adaptive immune responses, in particular T cells, in the pathology of this disease. Clinical trials involving active immunisation with Aβ in adjuvants resulted in development of meningoencephalitis in a subset of patients, which was associated with increased infiltration of T cells into the brain. Furthermore, Aβ-specific T cells have been identified in AD patients.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin